The visualization of a mountain using 3D printing - Jakub Wabiński (Biuletyn Wojskowej Akademii Technicznej, 2017)
Flat studies showing terrain (e.g. in form of maps) do not fully reflect its nature. Planning or design projects are definitely better represented in three-dimensional space. Previously used “sand tables”, especially popular in military applications, are expensive and uncomfortable to use due to their large size. In addition, they are modifiable only to a small extent and do not provide such accuracy as traditional maps. With the development of modern model relief techniques, a spectrum of the possibilities for development of customized spatial models (defined as models of the surrounding reality, mapped in the appropriate scale in three dimensions), has increased. The aim of this article is to present the possibilities of using 3D printing for the visualization of a mountain. Based on the digital terrain model (DTM), a model of a part of the Tatra Mountains was developed. It was established by DTM data processing and printing on a 3D printer using the FDM (Fused Deposition Modeling) technology. This article describes the principles for developing such a model and the advantages and disadvantages of the proposed solution. Keywords: cartography, digital terrain model, sand table, FDM technology